On non-ergodic Gaussian quadratic stochastic operators - Hamzah, Nur Zatul Akmar; Ganikhodjaev, Nasir (Institute of Physics Publishing, 2018)
In this paper, we construct a non-Volterra Gaussian Quadratic Stochastic Operators defined on the set of real numbers R and show non-ergodicity of this transformation.